Rapt in Plaid : Canadian Literature and Scottish Tradition - Waterston, Elizabeth, 1922- (Book collections on Project MUSE., 2001)
"Rapt in Plaid combines reflection, criticism, and memoir to illustrate a curious and long-lasting connection between Scottish and Canadian literary traditions. Examples drawn from genres including lyric poetry, narrative romance, war fiction, children's literature, sentimental fiction, thrillers, domestic novels, and short stories link Canadian writers such as John Richardson, Isabella Valancy Crawford, Sinclair Ross, Hugh MacLennan, Margaret Laurence, and W.O. Mitchell to Scottish writers such as Robert Burns, Walter Scott, Thomas Carlyle, J.M. Barrie, Robert Louis Stevenson, John Buchan, and George Mackay Brown."--Jacket